Modal Manusia Untuk Konservasi Waduk Wonogiri (Studi Kasus di Sub Daerah Aliran Sungai Keduang) - Maridi Maridi (Bioedukasi: Jurnal Pendidikan Biologi, 2011)
ABSTRACT- The purpose of this research is to know the level of human capital in    Sub-Watershed Keduang related to conservation efforts in the watershed. Based on the questionnaires on human capital in the watershed Keduang, levels of achievement of   particular capital at Keduang can be measured. The survey shows that 34.48% farmers of sub Watershed Keduang is considered as low educated. The level of human capital is 40.70 with a standard deviation of 6:51. If the total score of the ideal criteria is 55 the   actual level of human capital is considered as moderate. Such degree of human capital is considered as sufficiently support efforts in watershed management at Keduang.